Taxa de câmbio de equilíbrio e desalinhamento cambial: evidências para o Brasil (1994-2011) - Oliveira Damasceno, Aderbal (2018)
This paper estimates the equilibrium real effective exchange rate and the exchange rate misalignment for Brazil from 1994Q3 to 2011Q4. The paper contributes in three aspects: i) it calculates the real effective exchange rate series considering the twenty major trade partners; ii) the determinants of the real effective exchange rate are calculated relative to those of the twenty major trade partners; iii) it calculates a measure of current and total misalignment. The evidence indicates: overvalued exchange rate for the rigid exchange rate regime (1994Q3 to 1998Q4); undervaluation for the flexible exchange rate regime (1999Q1 to 2011Q4); undervaluation for the post subprime crisis (2008Q3 to 2011Q4) period; and an exchange rate overvaluation in 2011.